Academic performance and transversal competences in medical students, University of Carabobo, Venezuela - Everilda Arteaga Navas; Gilberto Antonio Bastidas Pacheco; Amilcar Josue Pérez Rivero (Universidad de La Rioja, 2021)
In Latin America, academic performance has shown high dropout rates, high repetition rates, a high number of students lagging behind in their studies, low grade point averages, and low graduation rates due to disarticulation with the student as a person, specifically in their studies. transversal competences. Descriptive, correlational, cross-sectional and field study. The population was 670 students in equal parts between the third and sixth year of the School of Medicine of the University of Carabobo, to whom a survey in Likert format was applied to measure transversal competences. 30% of the students were assumed as a sample, which implies 100 individuals for each group. The average age of the students was 21.4 } 2.7 years, the female gender (62%) prevailed over the male (38%), in both groups socioeconomic strata II and III prevailed. The transversal competences are perceived as deficient. In the description of academic performance and transversal competences, the relationships were mostly negative and of a very low degree, which indicates an inverse trend. Only with work performance and motivation were the correlations positive, also of a very low degree.